The role of meat in iron nutrition of vulnerable groups of the UK population - Fairweather-Tait, Susan (Frontiers in Animal Science, 2023)
Iron deficiency is a common public health problem in the UK. This review examines the role of meat in iron nutrition, focusing on the most vulnerable groups of the UK population. Meat contains haem iron which is absorbed by a different pathway to non-haem iron found in cereals and vegetables. A summary of absorption data from studies using isotopically-labelled haem iron shows that, although there is a wide degree of variation, haem iron bioavailability is consistently higher than non-haem iron. The importance of meat alternatives, such a plant protein, insects, and biofortified crops as a supply of bioavailable iron, and the use of food iron fortification is reviewed. Finally, the consequences of excluding meat from the diet in relation to dietary iron requirements is discussed.